A role for bone turnover markers β-CrossLaps (CTX) and amino-terminal propeptide of type I collagen (PINP) as potential indicators for disease progression from MGUS to multiple myeloma. Issue 10 (3rd October 2018) - Vallet, Sonia; Hoyle, Nicholas R.; Kyle, Robert A.; Podar, Klaus; Pecherstorfer, Martin
Abstract: Multiple myeloma (MM) is characterized by bone lesions arising due to unbalanced bone remodeling. Changes in the bone formation marker amino-terminal propeptide of type I collagen (PINP) and the bone resorption marker β-CrossLaps (CTX) reflect physiologic bone turnover. Whether PINP and CTX have a role in disease progression from monoclonal gammopathy of undetermined significance (MGUS) to MM is unknown. In this cross-sectional follow-up study, 241 patients with MM or MGUS were included. Serum levels of PINP and CTX were significantly higher in MM patients compared to MGUS. Moreover, increasing concentrations of PINP and CTX were observed in those MGUS patients progressing to MM, whereas PINP and CTX levels remained unchanged in MGUS patients with stable disease. In conclusion, these data indicate a potential role of PINP and CTX as biomarkers for the progression of MGUS to MM.